2018
DOI: 10.1159/000487134
|View full text |Cite
|
Sign up to set email alerts
|

Children with a History of Premature Adrenarche Have Good Health-Related Quality of Life at the Age of 12 Years

Abstract: Background/Aim: Children with premature adrenarche (PA) are taller and more overweight than their healthy peers, and PA girls have a slightly accelerated pubertal development. There is some evidence that early exposure to androgens may have an influence on psychosocial development. The aim of this cross-sectional case-control study was to evaluate health-related quality of life (HRQoL) in PA children at the age of 12 years. Methods: The HRQoL was assessed for 43 PA (36 girls) and 63 control children (52 girls)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addition to a physical examination and blood tests, HRQoL was assessed with a generic 16D © HRQoL instrument, which is based on the respective adult version (15D © ) but developed and validated for adolescents aged 12 to 15 years. Several studies have shown that the instrument is valid in the sense that it produces credible results and is capable of differentiating between healthy adolescents and patients in a wide range of health problems (14)(15)(16)(17)(18)(19). The 16D includes 16 dimensions (vitality, sight, breathing, distress, hearing, sleeping, eating, discomfort and symptoms, speech, physical appearance, school and hobbies, mobility, friends, mental function, excretion and depression) with five response options for each.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to a physical examination and blood tests, HRQoL was assessed with a generic 16D © HRQoL instrument, which is based on the respective adult version (15D © ) but developed and validated for adolescents aged 12 to 15 years. Several studies have shown that the instrument is valid in the sense that it produces credible results and is capable of differentiating between healthy adolescents and patients in a wide range of health problems (14)(15)(16)(17)(18)(19). The 16D includes 16 dimensions (vitality, sight, breathing, distress, hearing, sleeping, eating, discomfort and symptoms, speech, physical appearance, school and hobbies, mobility, friends, mental function, excretion and depression) with five response options for each.…”
Section: Methodsmentioning
confidence: 99%